2015
DOI: 10.1155/2015/654721
|View full text |Cite
|
Sign up to set email alerts
|

Maslinic Acid Enhances Signals for the Recruitment of Macrophages and Their Differentiation to M1 State

Abstract: The inflammatory process is involved in the genesis and evolution of different diseases like obesity, cardiovascular disease, and cancer. Macrophages play a central role in inflammation. In addition, they can regulate some stages of cancer development. Macrophages can polarize into M1 or M2 functional phenotype depending on the cytokines present in the tissue microenvironment. On the other hand, triterpenes found in virgin olive oil are described to present different properties, such as antitumoral and anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…In our study, maslinic acid suppressed TNF-α and enhanced IL-1β in human U937 macrophages ( Fig. 4g and h), which is in alignment with observations by others [64][65][66][67]. The other two terpenoids identified in our study, α-amyrin and β-amyrin (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, maslinic acid suppressed TNF-α and enhanced IL-1β in human U937 macrophages ( Fig. 4g and h), which is in alignment with observations by others [64][65][66][67]. The other two terpenoids identified in our study, α-amyrin and β-amyrin (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The secretion of the inflammatory cytokines IL-6 and TNF-α from LPS-stimulated murine macrophages were significantly reduced (p < 0.01) by 50 μM and 100 μM of maslinic acid [65]. In THP-1 cells, maslinic acid enhanced the recruitment of macrophages by elevating the production of IL-8, IL-1α, and IL-1β [66]. Maslinic acid suppressed TNFα production in RAW264.7 cells, and maslinic acid had anti-inflammatory effects in carrageenan-induced paw edema model, as well as anti-arthritis effects in mice models of arthritis [67].…”
Section: Discussionmentioning
confidence: 94%
“…Although Sánchez‐Quesada et al. has reported that MA could prevent chronic inflammation by modulating macrophage differentiation between type I helper T cells and type II helper T cells in human acute monocytic leukemia cell line THP‐1 , as far as we know, this is the first report on the suppressive effect of MA on chronic inflammatory response in vivo. TNF‐α is one of the major inflammatory cytokines that has the capacity to activate prime neutrophils for their various functions .…”
Section: Discussionmentioning
confidence: 78%
“…This anti-tumor function, which has attracted the most attention [ 30 33 ], is reported to be closely related to apoptotic pathway [ 12 , 34 36 ] but the underlying mechanism remains to be elucidated. One study investigated the expression level of several inflammatory factors, allowing the authors to argue that MA exerts anti-tumor effect by preventing chronic inflammation which represents a crucial step in the development of some cancers [ 37 ]. However, the evidence of molecular mechanism is to be provided.…”
Section: Discussionmentioning
confidence: 99%